A simplified model for inelastic seismic analysis of RC frame have shear hinge in beam-column joints. (February 2021) - Khan, Muhammad Shoaib; Basit, Abdul; Ahmad, Naveed
Abstract: This paper presents a simplified beam-column joint modeling technique for the inelastic analysis of reinforced concrete moment-resisting frames. The joint model consists of a zero-length link element that is provided with moment-rotation lumped plasticity hinge, provided at the intersection of beam/column elements, to simulate the nonlinear shear behavior of the joint panel. The backbone of the moment-rotation constitutive law was defined using the empirical shear stress-shear strain relationship proposed by Kim and LaFave. The hysteretic response of the joint was simulated using the multi-linear hysteretic rule proposed by Sivaselvan and Reinhorn. The modeling technique was applied to two portal frames tested under quasi-static cyclic loads for predicting the cyclic force-displacement hysteretic response. The prediction was found in good agreement with the experimental response; the numerical models were efficient in simulating the shear behavior of the joints, loading/unloading stiffness and pinching behavior of the frames' lateral force-displacement hysteretic response. The modeling technique was extended to two-story frames for nonlinear response history analysis for both design base and maximum considered earthquakes. Inter-story drift demands were obtained and critically compared to highlight the efficacy of the accurate modelling of beam-column joint using lumped plasticity shear simulation hinges. The study also confirms the beneficial role of beam-column joint detailing in resisting both design base and maximum considered earthquakes without exceeding the life safety and collapse prevention limit states respectively.